Geneva medical students increasingly identify primary care physicians as role models after introduction of a compulsory clerkship. Issue 1 (1st January 2021) - Pfarrwaller, Eva; Abbiati, Milena; Baroffio, Anne; Haller, Dagmar M.
Abstract: Background: Role modelling is recognised as an important element in career choice. In strongly hospital-based medical education settings, students identify few primary care physicians as positive role models, which might impact their career plans and potentially contribute to primary care workforce shortage. At Geneva Faculty of Medicine (Switzerland), a compulsory final-year clerkship in primary care practices was introduced to strengthen primary care teaching in the curriculum. Objectives: To assess the proportion of graduating students identifying a primary care physician as positive role model, before and after the introduction of the clerkship. Methods: Cross-sectional survey in four consecutive classes of graduating medical students one year before and three years after the introduction of the clerkship. The main outcome measure was the proportion of students in each class citing a primary care physician role model. Comparisons were analysed using Pearson's Chi-square test and one-way ANOVA. Results: The total sample included 505 students. The proportion of students recalling a primary care physician role model increased steadily from 8% (before introduction of the clerkship) to 13, 16, and 21%, respectively, at 1, 2 and 3 years after the introduction of the clerkship ( p  = 0.03). Conclusion: Our exploratory study suggests that introducing a compulsory primary care clerkship may have contributed to increasing the visibility of primary care physicians as role models. Future research should explore primary care physicians' awareness of role modelling and its contribution to career choices.